2011
DOI: 10.1002/jwmg.176
|View full text |Cite
|
Sign up to set email alerts
|

Forage availability for white‐tailed deer following silvicultural treatments in hardwood forests

Abstract: Closed-canopy upland hardwood stands often lack diverse understory structure and composition, limiting available nutrition for white-tailed deer (Odocoileus virginianus) as well as nesting and foraging structure for other wildlife. Various regeneration methods can positively influence understory development; however, non-commercial strategies are needed to improve available nutrition in many stands, as some contain timber that is not ready to harvest and others are owned by landowners who are not interested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…Forage availability in timber harvest treatments increased up to tenfold in comparison to mature forest stands. Studies in similar regions of the southern Appalachians also reported increases in forage availability and NCC for white‐tailed deer following canopy disturbance (Beck and Harlow , Ford et al , Lashley et al ). Researchers in western forest systems have reported similar increases in summer forage availability and NCC for elk following timber harvest (Hett et al , Collins and Urness , Strong and Gates ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Forage availability in timber harvest treatments increased up to tenfold in comparison to mature forest stands. Studies in similar regions of the southern Appalachians also reported increases in forage availability and NCC for white‐tailed deer following canopy disturbance (Beck and Harlow , Ford et al , Lashley et al ). Researchers in western forest systems have reported similar increases in summer forage availability and NCC for elk following timber harvest (Hett et al , Collins and Urness , Strong and Gates ).…”
Section: Discussionmentioning
confidence: 93%
“…Forage availability decreased 5 years following complete canopy removal without additional disturbance at North Cumberland WMA. Previous research has reported forage availability in young hardwood forest stands decreases to levels similar to mature forest stands 6–8 years after canopy removal as hardwood regeneration advances to a point of canopy closure and reduces available sunlight to the understory (Lashley et al , McCord et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We based deer NCC estimates on a comparative forage quality and quantity index calculated via a constraints algorithm (Hobbs and Swift ). Therefore, we made no assumptions that the index obtained reflects absolute estimates of deer NCC but only relative estimates useful for comparing treatment effects (Hobbs and Swift , Stewart et al , Lashley et al ).…”
Section: Methodsmentioning
confidence: 99%